Analysis of the cost-effectiveness of liquid biopsy to determine treatment change in patients with her2-positive advanced breast cancer in Colombia (2020)
Background: Breast cancer is highly prevalent worldwide and leads to high health-care costs. HER2-positive subtype represents 30% of all breast cancers and is associated with a poor prognosis. Patients treated with anti-HER2 therapies frequently develop resistance and require pharmacological treatment change. Liquid biopsy is a minimally invasive and an easily accessible technique, with high sensitivity and specificity, to detect molecular treatment resistance even before the onset of clinical manifestations and can thus be used to reduce unnecessary anti-HER2 treatment costs. Objective: To evaluate the cost-effectiveness of using liquid biopsy (ctDNA detection) to determine treatment change in women with HER2-positive advanced breast cancer in Colombia. Methodology: We performed an economic evaluation using decision tree modeling and deterministic analyses based on literature search for first and second lines of treatment (trastuzumab, pertuzumab, docetaxel, and TDM1); resistance; outcomes; and sensitivity and specificity of tests detecting molecular resistance. The effectiveness was measured using quality-adjusted life year (QALY) score, and costs were obtained from databases with national validity, suppliers, the Colombian Drug Price Information System (SISMED), and local studies. Results: The use of liquid biopsy (ctDNA detection) with conventional treatment was more expensive and less effective than conventional treatment without liquid biopsy (US $177,985.35 and 0.533889206 QALY, respectively). The incremental cost with liquid biopsy was US $7,333.17 and the incremental effectiveness was 0.00042256 QALY relative to the conventional method. Conclusion: Including liquid biopsy in the treatment of HER2-positive advanced breast cancer was considered currently inapplicable in Colombia because it was not cost effective. Our results open a window of opportunity to improve the development and implementation of ctDNA testing in Colombia, potentially reducing current costs. More evidence is required on the utility of this test, depending on the financial capacity of Colombia and other countries.